Public Health Australia : An Introduction - Lawson, James S. and Bauman, Adrian E. (Beijing McGraw-Hill, 2009)
This second edition continues to provide students and diverse health professionals with an introduction to the principles and practices of Public Health within the Australian context. New to this edition is a chapter on introductory statistics as well as the inclusion of statistics in the narrative and anecdotes.
Include Index
Keywords: Public health -- Australia